Pore scale investigation of gaseous mixture flow in porous anode of solid oxide fuel cell. (15th July 2016) - Dang, Zheng; Xu, Han
Abstract: A two-fluid finite-difference LB (Lattice Boltzmann) model is developed for multi-component flow. Then, a pore scale LB model is further developed for multi-component flow in porous media with heterogeneous microstructure. Thus, the present LB model is independent on any structure statistical parameters of the porous media, which is contrary to the numerical methods assuming the porous media is homogeneous. Compared with existing LB models for multi-component flow in the SOFC (solid oxide fuel cell) anode, the present LB model is capable of simulating mixture flow with larger ratios of molecular weights, thus it is qualified to meet the fuel flexibility of the SOFC. By using this model, the mass transfer of gaseous mixture flow in a SOFC anode is studied and the local molar fraction distributions of gaseous mixture are obtained within the irregular porous anode directly. The influences of anode microstructure, dimensionless reaction flux and fuel composition on anode performance are investigated. The quantitative relationship between the porous microstructure and anode performance is obtained. Highlights: A two-fluid finite-difference LB model is developed for multi-component flow. Present LB model can simulate mixture flow with larger ratios of molecular weights. A pore scale LB model is developed for mixture flow in heterogeneous porous media. The effect of heterogeneity of microstructure on mass transfer in anode is studied.